Identification of Flight Area Identification Plate Based on an Improved MSER Algorithm - Hao Liu; Daiwu Zhu; Yuran Zhu; Xiaofan Xie; Haodi Zhao (International Journal of Aerospace Engineering)
In this study, an algorithm based on improved maximum stable extremum region (MSER) was used to match and recognize the content of signage in the airfield, so as to overcome unrecognizable signage caused by low visibility or an overlapping field of view of multiple aircrafts. Firstly, the MSER algorithm was employed to combine regional structure similarity with feature space to realize the matching and recognition of signage in airport flight areas and improve the stability of signage content recognition. Secondly, the threshold of repeated recognition content was eliminated using the NMS algorithm to handle the repeated recognition caused by the MSER algorithm. Finally, an identification card of the taxiing paths in an airport flight area was selected for simulation. The experimental results demonstrated that the accuracy of identification card content can be improved by the optimized MSER algorithm.